How does leukemia disrupt hematopoiesis? - Thomas, A (2018)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy which, if left untreated, results in complete bone marrow (BM) failure characterised by anemia, neutropenia and thrombocytopenia. Although the symptoms of AML can occur at low levels of disease burden, their manifestation is often attributed to a loss of functioning hematopoietic cells via physical displacement. Evidence now suggests, however, that leukemic populations are capable of directly interfering with supportive BM niches and neighbouring hematopoietic cells. This therefore proposes that mechanisms unrelated to displacement may play a role in hematopoietic disruption during AML. A clinically accurate, kinetically tractable model of AML was generated through the transplantation of mutant Cebpa leukemic cells into recipient mice. At the onset of disease, committed BM erythroid progenitors were impaired immunophenotypically and functionally, and was an effect also observed hierarchically upstream in erythroid-forming Gata1-EGFP+ progenitors. In contrast, committed myeloid progenitors were expanded as a result of leukemic cell-expressed FLT3L and CCL6. Moreover, HSCs displayed no long-term defects in multi-lineage reconstitution once removed from the leukemic environment. Of note, sinusoidal BM vascular endothelial cells (VECs), demarcated by their expression of VCAM1, were reduced in frequency during leukemic development, whereas arteriolar VECs were expanded. Lastly, aged mice were capable of supporting leukemogenesis, which was accompanied by significant immunophenotypic and transcriptional changes to BM niches. Collectively, the findings presented in this study shed new light on the global immunophenotypic, functional and transcriptional changes that occur across several distinct BM populations during leukemia and ageing.